2016
DOI: 10.1021/jacs.6b08683
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear Cross-Relaxation under Solid-State Dynamic Nuclear Polarization

Abstract: We report on the spontaneous polarization transfer from dynamically hyperpolarized H toC during magic-angle spinning dynamic nuclear polarization (DNP) at temperatures around 100 K. The transfer is mediated by H-C cross-relaxation within methyl groups due to reorientation dynamics, and results in an inverted C NMR signal of enhanced amplitude. Further spreading of transferred polarization can then occur viaC-C spin-diffusion. The resulting process is equal to the nuclear Overhauser effect (NOE) where typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 27 publications
0
76
2
Order By: Relevance
“…[12] However, these features seem to be centered at the 13 C and 15 N Larmor frequency offsets which suggest cross-talk between the polarizations of different nuclear species, [8,25] or might be a sign of multiple nuclei undergoing concerted DNP transitions. Earlier studies have shown such features to occur at field offsets corresponding to nuclear combination frequencies, [26] a situation not given in this case.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[12] However, these features seem to be centered at the 13 C and 15 N Larmor frequency offsets which suggest cross-talk between the polarizations of different nuclear species, [8,25] or might be a sign of multiple nuclei undergoing concerted DNP transitions. Earlier studies have shown such features to occur at field offsets corresponding to nuclear combination frequencies, [26] a situation not given in this case.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…To quantify the DNP efficiency in 13 C direct polarization experiments, 13 C MAS experiments were recorded employing the saturation recovery pulse sequence. Since next to the direct polarization transfer to 13 C (direct channel), an alternative polarization pathway may occur, where polarization is transferred via the proton spin reservoir (indirect channel), [54][55][56][57][58] additional experiments with a pulse sequence containing rotor synchronized 180°pulses on the 1 H channel [57] were recorded. The spectra for the different 13 C MAS experiments are shown in Figure 6.…”
Section: Proof Of Radical Activity By Epr and Solid-state Dnp Nmrmentioning
confidence: 99%
“…[12] Furthermore,t his method is generally applicable to any system where isotope-labeled "reporter" methyl groups can be specifically introduced. We have shown that this effect can be used to specifically edit NMR spectra for high selectivity towards bound complexes in the presence of unbound species.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[9] These metal ions may specifically occupy endogenous binding sites, [10] or may be introduced into diamagnetic biomolecules by ac helate tag. [12] Besides the highly efficient, three-fold symmetric methyl reorientation, other molecular motions also seem to support this effect. [10] However,inthis case the close vicinity to the metal ion often causes NMR line broadening and thus al oss in resolution.…”
mentioning
confidence: 98%
See 1 more Smart Citation